MOLEKULAR DOCKING DENGAN METODE MOLEGRO VIRTUAL DOCKER TURUNAN KALKON SEBAGAI ANTIMIKROBA - Puspaningtyas, Ayik Rosita (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2012)
We have done docking molecule on chalcones derivatives that bind to antibacterial gram-positive (Bacillus subtilis ) and negative (Escherichia coli) compared with chalcones derivatives and chloramphenicol antibiotic. Chalcone derivatives compounds have been synthesized by varying the methoxy groups in chalcone structure. The results showed that chalcone derivatives have antibacterial activity in inhibition of Bacillus subtilis and Escherichia coli that were better than lead compound (chalcone) and chloramphenicol. The results can be viewed from Moldock and Rerank score that has lower energy. The results differ from in vitro study in 1 - (4-Bromo-phenyl) -3 - (4-phenyl-methoxy)-2-propen-1-on and 1-(4-Bromo-phenyl)-3-(3.4-dimethoxy-phenyl)-2-propen-1-on compounds as antibacterial activity in gram-negative bacteria (E. coli) and gram-positive bacteria (Bacillus subtilis) were smaller activity than chloramphenicol. Because of derivatives chalcones was very large lipophylic value (log P>2), these will decrease the activity. In addition, if these were viewed hydrogen bonds on Molegro Virtual Docker between chalcone derivatives and binding of bacterial amino acids, ie Lys 411, Ser 299, Ser 52, and Thr 412 in Bacillus subtilis and Tyr 136 and Tyr 52 in Escherichia coli provide less harmonious interaction within complex binding than that of chloramphenicol.